2006
DOI: 10.1002/gj.1062
|View full text |Cite
|
Sign up to set email alerts
|

The diversification and extinction of Doushantuo‐Pertatataka acritarchs in South China: causes and biostratigraphic significance

Abstract: The Ediacaran Period immediately follows the last Cryogenian glaciation-the $635 Ma Marinoan or Nantuo glaciation, and it is also punctuated by another brief glaciation-the $582 Ma Gaskiers glaciation. It is possible that these glaciations may have had significant impact on Ediacaran biological evolution (e.g. the appearance or disappearance of Doushantuo-Pertatataka acritarchs). Alternative hypotheses propose that the diversification of Doushantuo-Pertatataka acritarchs was caused by the Acraman bolide impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(15 citation statements)
references
References 74 publications
(87 reference statements)
0
14
0
Order By: Relevance
“…Elsewhere in the world Doushantuo-Pertatataka-type acanthomorphs occur generally in rocks that predate or are synchronous with carbon isotope excursions interpreted to be equivalent to the Shuram excursion (Zhou et al, 2007;Xiao et al, 2016;Zhou et al, 2017). The similarity between the Khesen assemblage reported here and that Publisher: GSA Journal: GEOL: Geology DOI:10.1130/G39576.1 Page 8 of 17 of the older Doushantuo Formation includes the presence of Appendisphaera grandis and A. tenuis, Cavaspina ?basiconica, Megasphaera, and Variomargosphaeridium gracile (Xiao et al, 2014b).…”
Section: The Age Of the Khesen Assemblagementioning
confidence: 60%
See 1 more Smart Citation
“…Elsewhere in the world Doushantuo-Pertatataka-type acanthomorphs occur generally in rocks that predate or are synchronous with carbon isotope excursions interpreted to be equivalent to the Shuram excursion (Zhou et al, 2007;Xiao et al, 2016;Zhou et al, 2017). The similarity between the Khesen assemblage reported here and that Publisher: GSA Journal: GEOL: Geology DOI:10.1130/G39576.1 Page 8 of 17 of the older Doushantuo Formation includes the presence of Appendisphaera grandis and A. tenuis, Cavaspina ?basiconica, Megasphaera, and Variomargosphaeridium gracile (Xiao et al, 2014b).…”
Section: The Age Of the Khesen Assemblagementioning
confidence: 60%
“…We have reworded this sentence to read: "Elsewhere in the world Doushantuo-Pertatataka-type acanthomorphs occur generally in rocks that predate or are synchronous with carbon isotope excursions interpreted to be equivalent to the Shuram carbon isotope excursion (Zhou et al, 2007;Xiao et al, 2016;Zhou et al, 2017)" for the reasons detailed in our response to the comment on lines 162-164 above. Please see lines 157-160 in the revised manuscript.…”
mentioning
confidence: 99%
“…Older reports of eukaryotic organisms are considered to be phylogenetically uncertain (Knoll 2003). On the other hand, the oldest widely accepted metazoan fossils only occur in the Doushantuo Formation, South China (Xiao et al 2000;Zhou et al 2001Zhou et al , 2007Chen et al 2004). Xiao (2004) suggested that there is no unequivocal metazoan fossils before the Neoproterozoic glaciation interval (ca.…”
Section: A Synthesis Of Early Metazoan Timescalementioning
confidence: 95%
“…2k) from Weng'an have been reviewed comprehensively by Xiao et al (2014b) and form part of the Doushantuo-Pertatataka microbiota (Zhou et al 2001(Zhou et al , 2007Liu et al 2014). The phylogenetic affinities of acritarchs are unknown and they probably represent a polyphyletic assortment of eukaryotes (Huntley et al 2006).…”
Section: Acritarchsmentioning
confidence: 99%